Analysis of Indicators of Fiscal Discipline in The IraqiEconomy for The Period 2003 - 2023 - Al-Wetaifi, Ahmed Saleh Kadhim Obais; Hamzah , Dr. Ali Falah; Eskander, Nabeel Takleef (International Journal of Accounting and Economics Studies, 2026)
The policy of Fiscal Discipline in most Arab countries, especially in Iraq, has been characterized by the absence of oversight and non-‎commitment to the application of the relevant standards and indicators in a correct and meaningful manner, mainly due to financial and ad-‎ministrative corruption and the absence of regulatory and legal regulation. This analytical study aims to evaluate the indicators of Fiscal ‎Discipline policies in Iraq and identify the most important obstacles that represent an obstacle to the progress of this policy and the difficul-‎ties it has been exposed to in the past and what it may be exposed to in the future by studying the indicators of Fiscal Discipline in Iraq and ‎showing their impact on economic activity.